Promoting the use of smart cards technology in Melaka / Mohd Roshadrimi Md Jani - Md Jani, Mohd Roshadrimi (2015)
Smart card technology remains novel for customers and merchants, in spite of several attempts by financial institutions to deploy the technology on wide scale bases. Evolution of lifestyle makes card technology been important to provides an interesting relationship and interactions between consumer and business than help to improve and simplify the process of payment. Melaka will become the first stage in the nation to implement electronic payment system in a few stages, an.d has acknowledge MyMelaka as the preferred choice of payment system in the historical city. MyMelaka payment systems ,wiII be implemented not only at the public transportation facilities in Melaka, but also covering theme parks, parking bays, as well as food and beverages outlets. The purpose of this study is to examine and analyze how advertising campaign can helps to promote the usage of MyMelalca Touch n' Go Cards. To research how to execute the advertising campaign, what direction and how to implement the idea of "Cashless City of Melaka". This paper also shows that MyMelaka Touch n' GO Smart Card technology can help between consumer and dealers in any sector such as transportation, food & restaurants, tourist spot, discussing at each step the opportunities and challenges.